Epidemiology of children with head injury: a national overview. Issue 6 (14th March 2016) - Trefan, L; Houston, R; Pearson, G; Edwards, R; Hyde, P; Maconochie, I; Parslow, RC; Kemp, A
Abstract : Background: The National Confidential Enquiry describes the epidemiology of children admitted to hospital with head injury. Method: Children (<15 years old) who died or were admitted for >4 h with head injury were identified from 216 UK hospitals (1 September 2009 to 28 February 2010). Data were collected using standard proformas and entered on to a database. A descriptive analysis of the causal mechanisms, child demographics, neurological impairment, CT findings, and outcome at 72 h are provided. Results: Details of 5700 children, median age 4 years (range 0–14.9 years), were analysed; 1093 (19.2%) were <1 year old, 3500 (61.4%) were boys. There was a significant association of head injury with social deprivation 39.7/100 000 (95% CI 37.0 to 42.6) in the least deprived first quintile vs. 55.1 (95% CI 52.1 to 58.2) in the most deprived fifth quintile (p<0.01). Twenty-four children died (0.4%). Most children were admitted for one night or less; 4522 (79%) had a Glasgow Coma Scale score of 15 or were Alert (on AVPU (Alert, Voice, Pain, Unresponsive)). The most common causes of head injury were falls (3537 (62.1%); children <5 years), sports-related incidents (783 (13.7%); median age 12.4 years), or motor vehicle accidents (MVAs) (401 (7.1%); primary-school-aged children). CT scans were performed in 1734 (30.4%) children; 536 (30.9%) were abnormal (skull fracture and/or intracranial injury or abnormality): 269 (7.6%) were falls, 82 (10.5%) sports related and 100 (25%). A total of 357 (6.2%) children were referred to social care because of child protection concerns (median age 9 months (range 0–14.9 years)). Conclusions: The data described highlight priorities for targeted age-specific head injury prevention and have the potential to provide a baseline to evaluate the effects of regional trauma networks (2012) and National Institute of Health and Care Excellence (NICE) head injury guidelines (2014), which were revised after the study was completed.